The impact of an invasive ambrosia beetle on the riparian habitats of the Tijuana River Valley, California - Boland,John M. (PeerJ, 2016)
The Tijuana River Valley is the first natural habitat in California to be substantially invaded by the Kuroshio Shot Hole Borer (KSHB, Euwallacea sp.), an ambrosia beetle native to Southeast Asia. This paper documents the distribution of the KSHB in the riparian vegetation in the valley and assesses the damage done to the vegetation as of early 2016, approximately six months after the beetle was first observed in the valley. I divided the riparian habitats into 29 survey units so that the vegetation within each unit was relatively homogenous in terms of plant species composition, age and density. From a random point within each unit, I examined approximately 60 individuals of the dominant plant species for evidence of KSHB infestation and evidence of major damage such as limb breakage. In the 22 forested units,I examined the dominant arroyo and black willows (Salix lasiolepis Benth. and S. gooddingii C.R. Ball), and in the seven scrub units, I examined mule fat (Baccharis salicifolia (Ruiz & Pav.) Pers.). Evidence of KSHB infestation was found in 25 of the 29 units. In the forest units, infestation rates ranged from 0 to 100% and were high (>60%) in 16 of the units. In the scrub units, infestation rates ranged from 0 to 33%. Infestation rates were significantly correlated with the wetness of a unit; wetter units had higher infestation rates. Evidence of major physical damage was found in 24 units, and dense stands of willows were reduced to broken trunks in several areas. Overall, I estimated that more than 280,000 (70%) of the willows in the valley were infested, and more than 140,000 had suffered major limb damage. In addition, I recorded evidence of KSHB infestation in the other common plant species in the valley; of the 23 species examined, 14 showed evidence of beetle attack. The four species with the highest rates of infestation were native trees in the Salicaceae family. The three species considered to be the worst invasive plants in the valley, Ricinus communis L., Tamarix ramosissima Ledeb. and Arundo donax L., had low rates of infestation. Several findings from this study have significance for resource managers: (1) the KSHB attack caused extensive mortality of trees soon after being first discovered so, if managers are to control the spread of the beetle, they will need to develop an effective early detection and rapid response program; (2) infestation rates were highest in units that were wet, so resource managers trying to detect the beetle in other areas should thoroughly search trees near water, particularly nutrient-enriched water; (3) the infestation appears to be a novel form of disturbance, and the affected forests may need special management actions in order to recover; and (4) the infestation has altered the structure of the forest canopy, and this is likely to promote the growth of invasive plant species that were relatively inconspicuous in the forests prior to the beetle attack but will now need more attention.
Keywords: Euwallacea; Riparian forest; Invasive species; Novel disturbance; Salix gooddingii; Kuroshio Shot Hole Borer; Salix lasiolepis